Polo‐like kinase 4 inhibitor CFI‐400945 suppresses liver cancer through cell cycle perturbation and eliciting antitumor immunity. Issue 3 (17th March 2023) - Chan, Cerise Yuen‐Ki; Yuen, Vincent Wai‐Hin; Chiu, David Kung‐Chun; Goh, Chi‐Ching; Thu, Kelsie L.; Cescon, David W.; Soria‐Bretones, Isabel; Law, Cheuk‐Ting; Cheu, Jacinth Wing‐Sum; Lee, Derek; Tse, Aki Pui‐Wah; Tan, Kel Vin; et al.
Abstract : Background and Aims: Prognosis of HCC remains poor due to lack of effective therapies. Immune checkpoint inhibitors (ICIs) have delayed response and are only effective in a subset of patients. Treatments that could effectively shrink the tumors within a short period of time are idealistic to be employed together with ICIs for durable tumor suppressive effects. HCC acquires increased tolerance to aneuploidy. The rapid division of HCC cells relies on centrosome duplication. In this study, we found that polo‐like kinase 4 (PLK4), a centrosome duplication regulator, represents a therapeutic vulnerability in HCC. Approach and Results: An orally available PLK4 inhibitor, CFI‐400945, potently suppressed proliferating HCC cells by perturbing centrosome duplication. CFI‐400945 induced endoreplication without stopping DNA replication, causing severe aneuploidy, DNA damage, micronuclei formation, cytosolic DNA accumulation, and senescence. The cytosolic DNA accumulation elicited the DEAD box helicase 41–stimulator of interferon genes–interferon regulatory factor 3/7–NF‐κβ cytosolic DNA sensing pathway, thereby driving the transcription of senescence‐associated secretory phenotypes, which recruit immune cells. CFI‐400945 was evaluated in liver‐specific p53/phosphatase and tensin homolog knockout mouse HCC models established by hydrodynamic tail vein injection. Tumor‐infiltrated immune cells were analyzed. CFI‐400945 significantly impeded HCC growth and increased infiltration of cluster of differentiation 4–positive (CD4 + ), CD8 + T cells, macrophages, and natural killer cells. Combination therapy of CFI‐400945 with anti–programmed death‐1 showed a tendency to improve HCC survival. Conclusions: We show that by targeting a centrosome regulator, PLK4, to activate the cytosolic DNA sensing‐mediated immune response, CFI‐400945 effectively restrained tumor progression through cell cycle inhibition and inducing antitumor immunity to achieve a durable suppressive effect even in late‐stage mouse HCC. Abstract :